UNDERSTANDING THE TRAVEL MOTIVATIONS OF POP CULTURE FANS - Veronique Labuschagne; Elizna Burger (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Popular culture (pop culture) events have the potential to promote tourist destinations and to generate tourism income. Travel motivation is a critical consideration for reaping these benefits since it serves as a stepping stone for event attendance and it initiates a desire to act. The purpose of this paper therefore is to determine the travel motivations of pop culture fans. Data was gathered from 576 pop culture fans attending a pop culture event in Gauteng, South Africa, using a structured questionnaire.  The data were analysed using exploratory factor analysis. The findings revealed nine travel motivations which were labelled brand visibility, event participation, acquire pop culture knowledge, escapism, celebrity fandom, value for money, exclusive merchandise, social enjoyment and novelty. The paper highlights novelty as the most important travel motivation for attending the specific pop culture event and it is therefore argued that pop culture fans attend these events to experience something new and different. In line with the findings of this research, it is recommended that pop culture event marketers pay close attention to all nine identified travel motivations to retain their current fans and to remain competitive.